Comparison of QTc Interval Before and After Hydroxychloroquine Therapy in Covid-19 Patients at Kendari City Hospital - Jamaluddin; Yusuf Musafir Kolewora; Ditha Arisqa Nasir (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Corona Virus Disease 19 (COVID-19) is caused by SARS-COV 2 which is of global public health concern. Hydroxychloroquine is a drug that is thought to be useful in treating COVID-19, but the mechanism of action of this drug is to block potassium channels and potentially extend the QTc interval. The purpose of this study was to determine the difference in QTc intervals before and after hydroxychloroquine therapy in COVID-19 patients at Kendari City Hospital. Methods:. This research is an observational analytic study, with a cross-sectional design, which was conducted at the Regional General Hospital of Kendari City. The number of samples in this study were 106 patients. Qtc interval values ​​before and after hydroxychloroquine therapy were collected using medical record data according to the inclusion criteria. Data was processed using paired t test analysis. Results: Bivariate analysis showed that there was a difference in the average Qtc interval before and after hydroxychloroquine therapy (409.02 vs 426.10, p<0.05). Conclusion:. There are differences in QTc intervals before and after hydroxychloroquine therapy in COVID-19 patients at Kendari City Hospital